The Authority of Customary Institutions in Dispute Resolution for Community Reconciliation - Lili Suarni; Faisal Efendi; Afrikal Candra; Titik Alfurqan; Dea Pita Sari; Melati Melati (CV Edujavare Publishing, 2026)
Under prevailing national law, dispute resolution typically occurs through a formally regulated court process. However, this formal system has often failed to satisfy the parties involved or other seekers of justice. Sources of dissatisfaction include the lengthy duration, high costs, and a process that is consistently convoluted and rigid. To address these issues, one alternative is to revitalize existing community-based customary institutions—ranging from the *kaum* (extended family/lineage) and *suku* (clan) levels to the *Kerapatan Adat Nagari* (KAN/Village Customary Council)—thereby achieving the desired justice through a process where there are no winners or losers. The research aims to identify the types of disputes handled by these customary institutions, understand the dispute resolution processes employed, and determine the obstacles faced by these institutions during resolution. This study employs a socio-legal research approach, with data collected through observation, interviews, and documentation. The findings indicate that the types of disputes handled at the *kaum* level include *sako* (customary titles/rights), *pusako* (ancestral property), inheritance, divorce, boundary disputes, sales and purchases, debts, and criminal matters. Similarly, at the *suku* (clan) level, the disputes or conflicts that frequently arise are the same: *sako*, *pusako*, inheritance, divorce, boundary disputes, sales and purchases, debts, and criminal matters. However, at the *Kerapatan Adat Nagari* (KAN) level, the disputes are limited to only two types: *sako* and *pusako*. Regarding the resolution process, at the *kaum* level, disputes are settled in a familial manner involving members of the same lineage through deliberation (*musyawarah*), with the *Mamak Kaum* or *Andiko Ketek* acting as the arbitrator or mediator. At the *suku* level, the process involves a third party from outside the disputing group—a procedure known as *Musyawarah Suku* (Clan Deliberation)—with a *Mamak Adat* holding the title of *Datuk* serving as the arbitrator or mediator. At the *Kerapatan Adat Nagari* (KAN) level, the process is as follows: The proceedings are opened by the KAN Secretary, followed by opening remarks from the KAN Chairperson; the KAN Chairperson then hands the proceedings over to the customary tribunal; a question-and-answer session takes place involving the tribunal head, the plaintiff, the defendant, and the panel of adjudicators; the panel deliberates; a site visit is conducted; both parties report whether or not they accept the site visit findings; a preliminary record of proceedings is drafted; and finally, a definitive ruling is issued. Research findings indicate that the customary institutions within the *Nagari* continue to play a role in resolving disputes at the community level. However, obstacles frequently encountered during the dispute resolution process include: first, issues stemming from the parties themselves, such as egoism and an inability to articulate their positions clearly; second, limitations among the ninik mamak (customary leaders), who may lack the analytical skills and experience necessary to provide effective solutions; and third, challenges at the Kerapatan Adat Nagari (KAN) level, such as data issues, a lack of professionalism, and instances where individuals hold vested interests in the dispute. Based on the foregoing, it is evident that customary institutions remain significant in resolving disputes within *Nagari* indigenous communities; thus, their existence must be safeguarded and preserved so that customary authority and institutions can endure alongside state institutions—which, while possessing greater legal certainty and formal power, do not always guarantee the delivery of the justice sought by the community.